2018
DOI: 10.1016/j.redox.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Short-term sustained hyperglycaemia fosters an archetypal senescence-associated secretory phenotype in endothelial cells and macrophages

Abstract: Diabetic status is characterized by chronic low-grade inflammation and an increased burden of senescent cells. Recently, the senescence-associated secretory phenotype (SASP) has been suggested as a possible source of inflammatory factors in obesity-induced type 2 diabetes. However, while senescence is a known consequence of hyperglycaemia, evidences of SASP as a result of the glycaemic insult are missing. In addition, few data are available regarding which cell types are the main SASP-spreading cells in vivo.A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 52 publications
2
105
0
Order By: Relevance
“…Similar results were later reproduced with various T2DM mouse models . However, because control animals were not treated with glucose‐lowering agents, it is not known whether these effects are the result of the specific activity of SGLT2 inhibitors or reflect the effective amelioration of hyperglycaemia, which, per se , fosters LGI . An elegant study showed that peritoneal macrophages secrete IL‐1β in a glucose‐dependent manner in response to feeding and post‐prandial glycaemic spikes.…”
Section: Evidence Of the Anti‐inflammatory Effect Of Sglt2 Inhibitorsmentioning
confidence: 51%
See 1 more Smart Citation
“…Similar results were later reproduced with various T2DM mouse models . However, because control animals were not treated with glucose‐lowering agents, it is not known whether these effects are the result of the specific activity of SGLT2 inhibitors or reflect the effective amelioration of hyperglycaemia, which, per se , fosters LGI . An elegant study showed that peritoneal macrophages secrete IL‐1β in a glucose‐dependent manner in response to feeding and post‐prandial glycaemic spikes.…”
Section: Evidence Of the Anti‐inflammatory Effect Of Sglt2 Inhibitorsmentioning
confidence: 51%
“…[55][56][57][58][59] However, because control animals were not treated with glucose-lowering agents, it is not known whether these effects are the result of the specific activity of SGLT2 inhibitors or reflect the effective amelioration of hyperglycaemia, which, per se, fosters LGI. 32,60 An elegant study showed that peritoneal macrophages secrete IL-1β in a glucose-dependent manner in response to feeding and post-prandial glycaemic spikes. IL-1β stimulates insulin secretion, and together they act on macrophages to induce glucose uptake, and insulin sustains a pro-inflammatory gene expression profile.…”
Section: Evidence Of the Anti-inflammatory Effect Of Sglt2 Inhibitomentioning
confidence: 99%
“…Catalase, one of SIRT1's downstream antioxidant enzymes, is decreased in H 2 O 2 ‐induced premature senescence . Human SOD‐2 and mouse SOD‐1 are antioxidant enzymes and play an important role in the prevention of endothelial senescence and inflammation . Previous reports indicated a reciprocal positive feedback regulation between SIRT1 and eNOS .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence is suggesting a bidirectional interplay among EC metabolism and ARDs (Graupera and Claret, 2018). One of the most characterized metabolic alteration in ECs exposed to hyperglycemia, i.e., a known senescencepromoting stimulus (Prattichizzo et al, 2018a), is the diversion of glycolytic intermediates into alternate pathways (Figure 2). This is the result of the activation of the enzyme polyADP-ribose polymerase 1 (PARP1) following the ROS-induced DNA damage.…”
Section: Endothelial Cell Metabolism In Age-related Diseasesmentioning
confidence: 99%